Effect of polyvinyl chloride microplastic on haematological of tilapia (Oreochromis niloticus) - Setyono, Bagus Dwi Hari; Soenarky, Wiwin Iky; Abidin, Zaenal; Affandi, Rangga Idris (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2026)
Plastic is the material most widely used by humans in life and commercial activities. The plastic waste used will ultimately be disposed of into the aquatic environment. Floating particles of plastic waste accumulate in pelagic habitats and form large waste patches. Meanwhile, non-floating debris degrades in the water column and in sediment, forming microplastics. Microplastics are small plastic waste measuring <5 mm. One type of microplastic that has an adverse impact on the life of organisms in waters is polyvinyl chloride (PVC). The aim of this research is to determine the effect of polyvinyl chloride microplastic exposed on haematological of tilapia, so it is hoped that a solution will emerge that can deal with this microplastic problem. This study was conducted in a completely randomized design (CRD) consisting of four treatments with three replications. The treatments were as follows: MP0 = No addition of microplastics (control); MP1 = Addition of 5 mg/L microplastics; MP2 = Addition of 15 mg/L microplastics; MP3 = Addition of 20 mg/L microplastics. Data were analyzed using SPSS version 25, with results expressed as mean ± standard error, and differences between control and treatments assessed by one-way ANOVA followed by Duncan’s multiple range test at a significance level of P<0.05. The conclusion is exposure to polyvinyl chloride microplastics on the haematological of tilapia through water made a real difference to erythrocytes, leukocytes, lymphocytes, monocytes, neutrophils, hematocrit, haemoglobin, and glucose.